2020
DOI: 10.1186/s12891-020-03540-7
|View full text |Cite
|
Sign up to set email alerts
|

Gorham-Stout disease successfully treated with sirolimus (rapamycin): a case report and review of the literature

Abstract: Background: Gorham-Stout disease (GSD) is a rare disease characterized by bone lesions and osteolysis. Therapy usually involves surgical resection. Sirolimus (Rapamycin) is used in some patients with GSD but the efficacy and safety of Sirolimus remains unclear. We propose that Sirolimus may be a novel therapeutic for GSD and present a case and review of literature that supports this. Case presentation: We presented a 1-year-old boy with GSD involving osteolysis of the right humerus with fracture of the left fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…An increase of the number of Treg is achievable by Treg transfer or treatment with mTOR (mammalian target of rapamycin) inhibitors (von Boehmer and Daniel, 2013). Recent studies (Ozeki and Fukao, 2019;Ricci et al, 2019;Liang et al, 2020) reported that effectiveness of mTOR inhibitor Sirolimus in the treatment of GSD patients; indeed Sirolimus is known to inhibit lymphangiogenesis and is thought to act on lymphatic tissue within lesions regulating production and leakage of lymph (Ozeki and Fukao, 2019). Sirolimus also stimulates Treg (Battaglia et al, 2006;Strauss et al, 2009), that according with our results, could inhibit bone erosion.…”
Section: Discussionsupporting
confidence: 82%
“…An increase of the number of Treg is achievable by Treg transfer or treatment with mTOR (mammalian target of rapamycin) inhibitors (von Boehmer and Daniel, 2013). Recent studies (Ozeki and Fukao, 2019;Ricci et al, 2019;Liang et al, 2020) reported that effectiveness of mTOR inhibitor Sirolimus in the treatment of GSD patients; indeed Sirolimus is known to inhibit lymphangiogenesis and is thought to act on lymphatic tissue within lesions regulating production and leakage of lymph (Ozeki and Fukao, 2019). Sirolimus also stimulates Treg (Battaglia et al, 2006;Strauss et al, 2009), that according with our results, could inhibit bone erosion.…”
Section: Discussionsupporting
confidence: 82%
“…Main therapies consist of surgical excision and reconstruction of bone tissue, radiotherapy, and sirolimus (rapamycin) treatment. Rapamycin treatment represents a novel approach whose safety and efficacy remain unclear [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This option could be particularly useful in younger patients, who might not tolerate well other therapeutic regimens, as radiotherapy, bisphosphonates or interferon. 7 Hou et al 8 have shown, through lymphoscintigraphy, that chylous effusion, observed in up to a quarter of patients with this condition, occurs because of occlusion of the thoracic duct and lymphatic hyperplasia in the pleura and thoracic bones. Chylothorax carries a 69% mortality rate, due to massive protein loss, in those treated with medical management alone, and a 36% rate if surgical intervention is attempted.…”
Section: Discussionmentioning
confidence: 99%